Tutorial: Designing multi-projetor VR systems: from bits to bolts - Soares, L. P.; Bruno R. de Araujo; Jorge, J.; Dias, J.; Raposo, A.; Carvalho, F. (Atas do 23RD SIBGRAPI 2010, 2010)
This tutorial will present how to design, construct and manage immersive multi-projection environments, covering from projection technologies to computer hardware and software integration. Topics such as tracking, multimodal interactions, and audio will be explored. In the end, we will present essential design decisions from actual cases.